A Madness to Our Method: Congregational Studies as A Cross-Disciplinary Approach to Contextualizing Teaching and Learning in Theological Education - Mercer, Joyce Ann (Teaching theology and religion, 2006)
This article explores congregational studies as a valuable teaching tool for contextualizing theological education across disciplines. As a form of pedagogy, congregational studies situates learning in a particular local ministry context. In addition, such a pedagogy apprentices learners within a particular “community of practice”– namely, that of professional church leaders of various types (lay, clergy, professional educators, etc.) having the knowledge and skills that allow them to read diverse contexts of ministry and improvise appropriate and faithful strategies of action within those contexts. After describing one seminary teaching experience in which congregational studies methods formed the pedagogical framework for an interdisciplinary course on the Bible and religious education, the article puts forward a practice-based theory of adult learning to explain why congregational studies methods are particularly helpful to adult learners engaged in theological education. The article concludes by briefly addressing some problems and limitations to pedagogical processes based upon congregational studies. (The research for this article and its writing were supported by a grant from the Wabash Center for which I am deeply appreciative. An earlier version of this article was presented at the 2004 Annual Meeting of the American Academy of Religion’s Academic Teaching and the Study of Religion Section.)